Sport satisfaction in physical education classes: A descriptive quantitative study of junior high schools in Bengkulu City - Yahya Eko Nopiyanto; Cahyo Wibowo; Ipa Sari Kardi; Defliyanto Defliyanto; Rahmawan Santoso; Bojan Bjelica; Yarmani Yarmani (Universitas Sriwijaya, 2025)
This study describes junior high school students’ sports satisfaction in physical education classes. Using a quantitative descriptive approach with a cross-sectional survey design, the study involved 234 junior high school students enrolled in physical education subjects. The Sports Satisfaction Instrument (SSI) was administered to collect data related to students’ levels of sports satisfaction during PE learning. The results were analyzed using descriptive statistical techniques, with satisfaction levels categorized into very high, high, medium, low, and very low. The findings revealed that 224 students were in the very high satisfaction category, eight students were in the high category, two students were in the medium category, and none were classified as low or very low. Overall, these results indicate that junior high school students in Bengkulu City experience sports satisfaction at a very high level. This study provides a strong foundation for developing and maintaining a pleasant, engaging, and sustainable physical education environment that supports students’ positive experiences and participation.